2020
DOI: 10.1152/ajpgi.00178.2019
|View full text |Cite
|
Sign up to set email alerts
|

Numb negatively regulates the epithelial-to-mesenchymal transition in colorectal cancer through the Wnt signaling pathway

Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors and is associated with a high mortality rate due to the lack of specific biomarkers available for early diagnosis, targeted therapies, and prognostic surveillance. In the present study, we investigated the function of Numb and its underlying mechanism in CRC. Immunohistochemical staining and clinicopathological analysis were used to assess the expression of Numb and its clinical significance in patients with CRC. Quantitative real-time polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…We used GO and KEGG enrichment analyses to explore the functions of the DEGs identified by overlapping the DEGs in the 3 datasets. GO analysis indicated that negative regulation of growth, bicarbonate transport, and transporter activity ( 38 40 ) were closely related to the development and growth of cancer; some KEGG pathways, such as nitrogen metabolism and retinol metabolism, were also linked to the pathogenesis of CRC. Nitrogen is an essential biomolecule in humans and regulates cellular metabolism, and retinol is a form of vitamin A closely related to immune functions ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used GO and KEGG enrichment analyses to explore the functions of the DEGs identified by overlapping the DEGs in the 3 datasets. GO analysis indicated that negative regulation of growth, bicarbonate transport, and transporter activity ( 38 40 ) were closely related to the development and growth of cancer; some KEGG pathways, such as nitrogen metabolism and retinol metabolism, were also linked to the pathogenesis of CRC. Nitrogen is an essential biomolecule in humans and regulates cellular metabolism, and retinol is a form of vitamin A closely related to immune functions ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that the Wnt signaling pathway contributes to increased invasion and malignancy of tumor cells via EMT induction [258][259][260]. The inhibition of Wnt by onco-suppressor factor Numb suppresses EMT in cancer cells, thereby illustrating the role of Wnt as an upstream mediator of EMT [261]. In addition, EMT induction by Wnt can elevate proliferation of cancer cells, and triggers their resistance into apoptosis [262].…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…Numb was widely reported as a tumor suppressor in various cancers, and low expression of Numb was related to highly malignant tumor cells ( 21 , 28 , 50 , 51 ). As shown in our data, there was reduced expression of Numb at the protein level, suggesting the involvement of ubiquitination and protein degradation ( 29 , 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%